The influence of leadership style, organizational culture, and work stress on employee work productivity at PT. Kahatex Cimahi - Siti Susanti; Gurawan Dayona Ismail; Yoyo Sudaryo; Mochammad Mukti Ali; Erna Herlinawati; Dadan Abdul Aziz (Jurnal Scientia, 2024)
This study aims to determine the influence of the simultaneous or partial variables of leadership style, organizational culture, and work stress on employee work productivity at PT. Kahatex Cimahi. In this study, the sample was employees of PT. Kahatex Cimahi with a total sample of 85 people. This study used quantitative methods with random sampling techniques. The data analysis tool uses the SPSS program version 25.0. Based on the results of research at PT. Kahatex Cimahi shows that leadership style, organizational culture, and work stress partially and simultaneously affect employees' work productivity.